Activities Of School Violence Prevention In Viet Nam: A Case Of Thai Nguyen City Junior High Schools, Thai Nguyen Province, Vietnam - SAU, NGUYEN THI; HA, NGUYEN VIET (The journal of contemporary issues in business and government, 2021)
The age of middle school students is the age that is forming personality values. This is the transition period from children to adults, is the period of formation of personality values, rich in dreams, like to explore and explore, but lack of social understanding, lack of life experience, easy being manipulated and easily provoked, etc. Especially in the context of international integration, the market mechanism along with the explosion of information, the young generation is often affected by mixed positive and negative factors always placed in the situation of choosing values, coping with difficulties, challenges, and negative pressures, making the young generation show many signs of misconceptions and live away from prices. traditional ethical treatment, can be attracted to negative behaviors, violence, selfish lifestyle, hybrid, pragmatic, easy to develop personality deviation. The article researches and gives some solutions to limit current school violence and bring a better environment.